Spelaeobochica goliath (Arachnida: Pseudoscorpiones: Bochicidae), a new troglobitic pseudoscorpion from Brazil - Viana, Ana Clara M.; Souza, Maysa F. V. R.; Ferreira, Rodrigo L. (Zootaxa, 2018)
Spelaeobochica goliath sp. n., found in a limestone cave located in the municipality of Ibiracatu (Minas Gerais, Brazil), is described. It can be distinguished from the other species of the genus mainly by the slight angular shape of the anterior margin of the carapace, distal position of the trichobothrium est relative to st on the movable finger, isb in a position much nearer to level of sb than to that of esb, and by its pedipalpal measurements and proportions. It shares many morphological features with S. iuiu.